2015
DOI: 10.1515/sjecr-2015-0005
|View full text |Cite
|
Sign up to set email alerts
|

Early Cytokine Profile Changes In Interstitial And Necrotic Forms Of Acute Pancreatitis

Abstract: Acute pancreatitis (AP) is a common, potentially lethal, acute inflammatory process with a highly variable clinical course. The aim of this study was to analyse early changes in the serum concentrations of pro- and anti-inflammatory cytokines in the peripheral blood of patients with the interstitial form of acute pancreatitis (IAP) and necrotic acute pancreatitis (NAP), especially in those patients who had lethal outcomes.The prospective study enrolled 52 patients who were divided into IAP (65.38% of patients)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…The study by Kay et al [ 20 ] suggests that the initial inflammatory response in AP develops as naive Th17 cells are generated in response to macrophage-derived IL-6 [ 20 ], whereas the development of SAP occurs as a result of Th17 response with a greater pathogenic potential (IL-23 induced), probably due to dysfunctional autophagy or the inability of monocytes to mount an adequate IL-10 anti-inflammatory response due to anergy [ 20 ]. Moreover, Kostic et al [ 21 ] have demonstrated that IL-6, IL-8, and IL-10 levels in the first three days of AP are accurate markers of necrosis and of a potentially lethal outcome. Observations made by Kostic et al [ 21 ] of significantly higher IL-6 levels in patients with necrotizing AP, remain consistent with the results presented in this article.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The study by Kay et al [ 20 ] suggests that the initial inflammatory response in AP develops as naive Th17 cells are generated in response to macrophage-derived IL-6 [ 20 ], whereas the development of SAP occurs as a result of Th17 response with a greater pathogenic potential (IL-23 induced), probably due to dysfunctional autophagy or the inability of monocytes to mount an adequate IL-10 anti-inflammatory response due to anergy [ 20 ]. Moreover, Kostic et al [ 21 ] have demonstrated that IL-6, IL-8, and IL-10 levels in the first three days of AP are accurate markers of necrosis and of a potentially lethal outcome. Observations made by Kostic et al [ 21 ] of significantly higher IL-6 levels in patients with necrotizing AP, remain consistent with the results presented in this article.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Kostic et al [ 21 ] have demonstrated that IL-6, IL-8, and IL-10 levels in the first three days of AP are accurate markers of necrosis and of a potentially lethal outcome. Observations made by Kostic et al [ 21 ] of significantly higher IL-6 levels in patients with necrotizing AP, remain consistent with the results presented in this article.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations